AN EFFECTIVE EXTENSION SYSTEM TO IMPROVE THE BEHAVIOR OF BALI CATTLE BREEDER IN BALI - Tatik Inggriati, Ni Wayan; Suparta, I Nyoman; Suarna, I Wayan; Antara, I Made (E-Journal Of Animal Science Udayana University, 2014)
A survey was carried out to determine the behavior of bali cattle breeders in Bali, as well as finding an effective extension system in implementing technic and management production. The research design was a survey, using a questionnaire as a data collection tool. Research was conducted in all eight regencies and one city in Bali. In total 198 breeders were surveyed by purposive sampling method, 99 of which were members of groups and 99 were not members of groups. Data was analyze using  descriptive, t-test, and Structural Equation Model (SEM). Results of the research showed that: 1) The level behavior, bali cattle breeders in implementing technical and production management classified in the middle category; 2) The extension system in Bali for bali cattle breeders to improve the behavior was not effective; and 3) Effective extension system to improve bali cattle breeders behavior is extension conducted by a professional extension workers, with an innovative extension materials, reliable extension institution, and adequate extension financing, through a group approach. Based on the research results, it is suggested that: 1) the Government should to improve the professionalism of extension workers, innovative extension materials, forming reliable extension institution, and provide adequate extension financing; 2) Breeders is to become an active member of groups breeder.